2007
DOI: 10.1021/bi701921b
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Activation Protein Peptide Substrates Identified from Human Collagen I Derived Gelatin Cleavage Sites

Abstract: A highly consistent trait of tumor stromal fibroblasts is the induction of the membrane-bound serine protease fibroblast activation protein-α (FAP), which is overexpressed on the surface of reactive stromal fibroblasts present within the stroma of the majority of human epithelial tumors. In contrast, FAP is not expressed by tumor epithelial cells or by fibroblasts or other cell types in normal tissues. The proteolytic activity of FAP, therefore, represents a potential pan-tumor target that can be exploited for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
90
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 28 publications
(60 reference statements)
6
90
1
Order By: Relevance
“…Despite a lack of direct evidence, FAP is assumed to degrade ECM components, including type I collagen in vivo (9,22,23). In support of this idea, we have observed that FAP deficiency leads to increased tumor collagen content in a syngeneic transplant model of colon cancer and an endogenous K-ras-driven murine lung tumor model (24).…”
mentioning
confidence: 58%
See 2 more Smart Citations
“…Despite a lack of direct evidence, FAP is assumed to degrade ECM components, including type I collagen in vivo (9,22,23). In support of this idea, we have observed that FAP deficiency leads to increased tumor collagen content in a syngeneic transplant model of colon cancer and an endogenous K-ras-driven murine lung tumor model (24).…”
mentioning
confidence: 58%
“…FAP has also been detected on pericytes, bone marrow-derived mesenchymal stem cells (18,19), and a small population of macrophages (20,21 FAP's in vivo substrates remain unclear. Despite a lack of direct evidence, FAP is assumed to degrade ECM components, including type I collagen in vivo (9,22,23). In support of this idea, we have observed that FAP deficiency leads to increased tumor collagen content in a syngeneic transplant model of colon cancer and an endogenous K-ras-driven murine lung tumor model (24).…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…8 FAP is a membrane-bound glycoprotein belonging to the serine protease family that has been demonstrated to cleave gelatin and human collagen I, and therefore has been implicated in the remodeling of the extracellular matrix. 9 It is normally expressed transiently in healing wounds, and abundantly by activated stromal fibroblasts in CRC and other human epithelial malignancies (breast, lung, and ovary carcinomas). 10 -12 Abundant FAP expression has been implicated as a negative prognostic factor in patients with metastatic CRC, 13 but its biological role is still not clear.…”
mentioning
confidence: 99%
“…CAFs are widely seen in breast and pancreatic cancer [81,82]. The overexpression of fibroblast activation protein-α (FAP) (membrane bound serine protease), on the CAFs, makes them different from the normal stromal cells [83]. FAP has a unique post-prolyl endopeptidase activity to cleave the dipeptide at NH2-terminal [84,85].…”
Section: Stromal Cellsmentioning
confidence: 99%